1.5 MW CW RF Loads for Gyrotrons - Ives Lawrence; Bui Thuc; Habermann Thomas; Collins George; Marsden David; Neilson Jeffrey; Horn Tim; Rock Chris (EPJ Web of Conferences, 2023)
A new series of MW-class, RF loads were developed that can dissipate power levels exceeding 1.5 MW at frequencies from 28 GHz to 180 GHz. The new loads are designed to reflect less than 0.25% of the input power and operate continuously (CW). Stainless-steel and anodized aluminum versions were developed. The stainless steel version is designed to meet requirements for nuclear facilities, such as ITER, while the aluminum version is capable of power levels exceeding 2 MW CW. The aluminum version is also lighter and less expensive. This paper describes the design and capabilities of the loads.